2022
DOI: 10.3390/ijms23063073
|View full text |Cite
|
Sign up to set email alerts
|

The Fight against Cancer by Microgravity: The Multicellular Spheroid as a Metastasis Model

Abstract: Cancer is a disease exhibiting uncontrollable cell growth and spreading to other parts of the organism. It is a heavy, worldwide burden for mankind with high morbidity and mortality. Therefore, groundbreaking research and innovations are necessary. Research in space under microgravity (µg) conditions is a novel approach with the potential to fight cancer and develop future cancer therapies. Space travel is accompanied by adverse effects on our health, and there is a need to counteract these health problems. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 223 publications
(445 reference statements)
2
25
0
Order By: Relevance
“…Significant changes in cell membranes, reorganization of the cytoskeleton, limited proliferation, and changes in protein and gene expression were observed [ 9 , 21 ]. Recent studies indicate that altered gravity induces shear stresses at the membrane surface, one of the essential factors in sensitizing cancer cells [ 22 ]. Additionally, our previous study showed morphological changes in cancer cells exposed to MG, i.e., stress fibers, membrane blebbing, and cytoskeleton reorganization [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Significant changes in cell membranes, reorganization of the cytoskeleton, limited proliferation, and changes in protein and gene expression were observed [ 9 , 21 ]. Recent studies indicate that altered gravity induces shear stresses at the membrane surface, one of the essential factors in sensitizing cancer cells [ 22 ]. Additionally, our previous study showed morphological changes in cancer cells exposed to MG, i.e., stress fibers, membrane blebbing, and cytoskeleton reorganization [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The similarities between our results and those of others using clinostats as earth-based analogs for simulating microgravity and partial-gravity conditions and results observed in space-flown sample in real microgravity, suggest that many of the reported effects might primarily be due to alterations in the modeled reduced gravity conditions. However, for the sake of scientific rigor, and as the mechanisms of gravisensing in SMG or SPG are as yet unclear 44 we would like to acknowledge the possibility that some of the phenomena observed in clinostats and the RPM could also be (in part) due to indirect effects in the environment (e.g., changes in fluid shear or mass transfer) 44 47 . Moreover, while differences in vibration, fluid shear, or mass transfer may occur between different path files in the RPM SW , these have yet to be quantified or identified as significant 25 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Microgravity has different effects on normal and cancer cells, but the related underlying mechanisms are still being elucidated. Experiments using normal or cancer cells performed in space on the International Space Station (ISS) or under s-µg-conditions using devices approved by ESA and NASA to create µg conditions on Earth (known as groundbased facilities) [131], belong to a newly evolving area of research in oncobiology [132]. Numerous studies have demonstrated how a short-and long-term exposure to r-and s-µg influences differentiation, proliferation, migration, survival, apoptosis, adhesion, and other processes involved in carcinogenesis [53].…”
Section: Effects Of Microgravity and Radiation On Gynecological Cance...mentioning
confidence: 99%